Comparison of vertical and horizontal reactive strength index variants and association with change of direction performance - Sarabon, N.; Kozinc, Z.; Bishop, C. (The Journal of Strength and Conditioning Research, 2023)
This study sought to investigate the interrelationship between different vertical and horizontal variants of reactive strength index (RSI) and change of direction (CoD) performance. Thirty-one male volleyball players (age: 22.4 ± 3.9 years) performed bilateral drop jumps (DJs), bilateral and unilateral countermovement jumps (CMJs), and triple hops for distance. The RSI was calculated as the ratio of jump height and contact time (DJ), jump height and time to takeoff (CMJ), flight time or hop distance and contact time (triple hop), and 505 CoD test. Reactive strength index obtained from DJ and CMJ tasks exhibited excellent trial-to-trial reliability (intraclass correlation coefficient [ICC] = 0.91-0.94), whereas triple hop-based RSI had only moderate reliability (ICC = 0.67-0.74). The relationships among different RSI variants were moderate to high (i.e., DJ to CMJ: r = 0.57-0.69, p = 0.004; DJ to triple hop: r = 0.54-0.66, p = 0.021; and CMJ to triple hop: r = 0.42-0.63, p = 0.037). For the triple hop, the associations between RSI based on hop flight time and RSI based on hop distance were high for hop 1-2 (r = 0.77-0.83; p < 0.001) and very high for hop 2-3 (r = 0.91-0.92; p < 0.001). All RSI variants were in small to moderate negative correlation with 505 test performance (r = -0.38 to -0.45; p = 0.042). The agreement in interlimb asymmetry direction between RSI from unilateral CMJ and triple hop RSI variables was slight to moderate (kappa coefficient = 0.06-0.36). In conclusion, although interrelationships between RSI variants were moderate to high, the direction of interlimb asymmetry was inconsistent, highlighting the notion of movement variability in limb dominance.